Formulasi Dan Uji Mutu Fisik Masker Gel Peel Off Kombinasi Sisik Ikan Bandeng Dan Ekstrak Kulit Buah Naga - Panji Ratih Suci; Ismi Karima Yulina; Valiandri Puspadina (An-Najat, 2024)
A peel-off gel mask is a topical preparation that is used by rubbing it on the face using with your hands or a brush which, if left for a while, can dry can dry and become firm so it can be removed. Milkfish scales contains collagen. The collagen content can be used as an antioxidant. Meanwhile, dragon fruit contains flavonoids has antioxidant properties by breaking down or inhibiting free radicals which are very reaktive and tend to from new radicals. This also works as a skin care product. Therefore, it is very good if it is formulated as a cosmetic product in the form of a peel-off gel mask. The method used in this research was the 70% alcohol maceration method. Contain milkfish scales of 0,3% and dragon fruit skin at concentrations of 1%, 3% and 5%. The physical quality test out included organoleptic tests, homogeneity tests, spreadability tests, drying time tests, and pH tests